Self-Healable, Fast Responsive Poly(ω-Pentadecalactone) Thermogelling System for Effective Liver Cancer Therapy - Shi, Huihui; Chi, Hong; Luo, Zheng; Jiang, Lu; Loh, Xian Jun; He, Chaobin; Li, Zibiao (Frontiers in Chemistry, 2019)
A polyurethane based thermogelling system comprising poly(ω-pentadecalactone) (PPDL), poly(ethylene glycol) (PEG) and poly(propylene glycol) (PPG), termed as PDEP, was synthesized. The incorporation of PPDL lowers critical micelle concentration (CMC) as well as critical gelation concentration (CGC) of the novel copolymers compared to commercial Pluronic® F127. The thermogels showed excellent thermal stability at high temperature up to 80 C, fast response to temperature change in a time frame of less than second, as well as remarkable self-healing properties after being broken at high strain. In vitro drug release studies using docetaxel (DTX) and cell uptake studies using doxorubicin (DOX) show high potential of the hydrogel as drug reservoir for sustainable release profile of payloads, while the in vitro anti-tumor evaluation using mice model of hepatocellular carcinoma further demonstrated the significant inhibition on the growth of tumor. Together with its excellent biocompatibility in different organs, the novel PDPE thermogelling copolymers reported in this work could potentially be utilized as in situ-forming hydrogels for liver cancer therapy.